Nanosystems for immune regulation against bacterial infections: a review - Zhang, Xiaodong (2022)
The immune system constitutes the fortifications that safeguard the body against bacterial infections. Artificial nanosystems possess many attractive properties including the ability to modulate the immune responses against bacterial infections. On the one hand, antigen-loaded nanosystems have emerged as a promising alternative to convensional vaccines, protecting the host from infection. On the other hand, immunity can be regulated by nanosystems to treat infections caused by bacteria and related diseases. Herein, we initially introduce the recent advances of artificial nanosystems in the development of different vaccines including subunit and toxoid vaccines. Then, we focus on discussing the employment of nanosystems for the activation of immunity, including innate and adaptive immunity, to treat bacteria-induced infectious diseases. In addition, nanosystems with immunosuppressive capabilities are also highlighted, which can restrain the overactivation of immune responses, thereby relieving inflammation in the face of infections. Finally, we discuss current challenges and provide perspectives for future development in this rapidly growing field. Thus, this review is expected to inspire more advanced research of using nanosystems to achieve immune regulation toward practical applications.